1988
DOI: 10.1007/bf00154740
|View full text |Cite
|
Sign up to set email alerts
|

The developmental changes of ERGs on spontaneous retinal degeneration of Celestial goldfish

Abstract: The Celestial goldfish, which belongs to the family of telescope-eye goldfish, displays unique spontaneous retinal degeneration associated with developmental anterodorsal protrusion of the eyeball. We observed concurrent changes in the electroretinogram. At the age of 75 days, the retinal layer was developed fully and the electroretinogram exhibited b-wave dominance similar to that of adult common goldfish. At the age of 105 days, when the eyeball began to protrude laterally, the b-wave amplitude decreased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Both celestial and telescope goldfish had suffered from visual function deficit, but the eye diseases were different between them. Celestial goldfish and goldfish with dragon's eyes both have abnormal functioning of the eyes, however, the development of celestial goldfish is accompanied by varying degrees of retinal degeneration [6], resulting in narrow vision and low light; Although the telescope goldfish 's eyeballs were protruding as well, its myopia was severe, and there was no retinal degeneration [49]. By comparative analysis, the albumin concentration in the vitreous humor of our celestial goldfish was higher than that of David's telescope goldfish [48], so it is speculated that probably celestial goldfish have a more severe degree of change in the condition of the membranes associated with the bloodretinal barrier than goldfish with dragon's eyes.…”
Section: Biochemical Components In Vitreous Humor Of the Celestial Go...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both celestial and telescope goldfish had suffered from visual function deficit, but the eye diseases were different between them. Celestial goldfish and goldfish with dragon's eyes both have abnormal functioning of the eyes, however, the development of celestial goldfish is accompanied by varying degrees of retinal degeneration [6], resulting in narrow vision and low light; Although the telescope goldfish 's eyeballs were protruding as well, its myopia was severe, and there was no retinal degeneration [49]. By comparative analysis, the albumin concentration in the vitreous humor of our celestial goldfish was higher than that of David's telescope goldfish [48], so it is speculated that probably celestial goldfish have a more severe degree of change in the condition of the membranes associated with the bloodretinal barrier than goldfish with dragon's eyes.…”
Section: Biochemical Components In Vitreous Humor Of the Celestial Go...mentioning
confidence: 99%
“…So far, few studies have been done on celestial goldfish, much of which has focused on their genetics and body color [3][4][5]. Some reports have also suggested that celestial goldfish have a degenerated retina and weak vision [6,7], making them suitable as model animals for the study of human eye diseases [8]. Blood is an crucial component of the fish organism and immune system [9], and blood indicators have historically been emphasized by production practitioners and theorists, and are frequently used to assess the health, nutrition, and environmental adaptation status of fish [10], as well as water quality monitoring [11].…”
Section: Introductionmentioning
confidence: 99%